Global lecture and learning series @ UiTMLaw - UiTM, Faculty of Law (Faculty of Law, 2023)
It is such, indeed, a great opportunity for a group of UiTM Law lecturers collaborating with our university partners, especially FMM Indonesia, and organizations to present certain topics on various issues on legal development from various aspects of law including Constitution law, contract law, cyber law, criminal law, intellectual property law, law of the sea, and environmental law.